Use of the normalized difference vegetation index (NDVI) to assess land degradation at multiple scales : current status, future trends, and practical considerations /: current status, future trends, and practical considerations. (2015) - Yengoh, Genesis T; Dent, David; Olsson, Lennart, 1955-; Tengberg, Anna; Tucker, Compton J
No abstract available